EVALUASI PEMAKAI TERHADAP KECOCOKAN TUGAS - TEKNOLOGI YANG MEMPENGARUHI KINERJA INDIVIDUAL (Studi Empiris pada Bank Pemerintah) - Irwansyah - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2011)
This research aims to identifying the relationship between task-technology fit and userevaluation, that influences individual performance. The hypothesis are; (1) The characteristic ofsystem information will affect user evaluation of task-technology fit; (2) The characteristic of task willaffect user evaluation of task-technology fit; (3) The characteristic of individual ability will affect userevaluation of task-technology fit; (4) The interaction between task, technology and individual willaffect user evaluation of task-technology fit; (5) User evaluation will affect individual performance.Research subject consist of 135 leaders from bank which implemented system informationtechnology. The data are analysed by regression (multiple and linier). The interaction on hypothesis4 are analysed by moderated regression analysis.Research finding shows; partially, the characteristic of information system, task andindividual ability will affect user evaluation. When the three variables on task-technology fit make aninteraction effect therefore user evaluations will have a better result. Another findings show userevaluation has a positive significant effect to individual performance. The conclusion from thisresearch is if user evaluation have a better result because of task-technology fit therefore individualperformance will improved indirectly.